2019
DOI: 10.21511/im.15(4).2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect customer loyalty in small enterprises

Abstract: The study was conducted by collecting the data from 608 customers of migrant retailers working in the retail industry of Pretoria West in South Africa in order to identify socioeconomic factors that affect customer loyalty. Data was collected from eligible respondents by using a pre-tested, validated and standardised questionnaire of study that was self-administered by respondents. The study found that about 69% of customers were loyal to their retailers. About 68% of customers had a favorable attitude towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Product selection recommendations are also more influenced by salespeople in retail stores where customers will buy products. In accordance with the opinion of Zeleke Worku's research, that customers are loyal to their retailers and loyal customers to the brand (products) offered by their retailers [52].The results of this study reveal guidelines for air conditioning company management to participate in activities that can contribute to customers and retail store salespeople including building brand associations and brand awareness to increase loyal air conditioning users to create a good corporate reputation for customers and retail store employees.…”
Section: Conclusion and Noveltysupporting
confidence: 84%
“…Product selection recommendations are also more influenced by salespeople in retail stores where customers will buy products. In accordance with the opinion of Zeleke Worku's research, that customers are loyal to their retailers and loyal customers to the brand (products) offered by their retailers [52].The results of this study reveal guidelines for air conditioning company management to participate in activities that can contribute to customers and retail store salespeople including building brand associations and brand awareness to increase loyal air conditioning users to create a good corporate reputation for customers and retail store employees.…”
Section: Conclusion and Noveltysupporting
confidence: 84%
“…At the same time, the authors pay attention to the training methods for obtaining relevant skills, which should include soft skills such as communication, negotiation, and conflict management to meet the requirements of creative entrepreneurship. Worku (2019) found that entrepreneurial skills and education significantly impact the profitability of all types of enterprises. The influence of teamwork, namely, internal (trust) and external (business contacts, external professional activity) relationships on the creativity of each participant was investigated by Long and Wang (2019).…”
Section: Theoretical Basismentioning
confidence: 99%
“…To hand over authority Edward (1975), Turkyilmaz et al (2011), Hassan et al (2013), Waqas et al (2014) 15 Participate in the decision-making process Waqas et al (2014) 16 Satisfaction Waqas et al (2014), Mai & Bui (2013) 17 Employee confidence in the business Nguyen (2010) 18 Knowledge of business operations of the enterprise Nguyen (2010) 19 Justice in the firm Nguyen (2010) To some extents, there have been some other researches related to loyalty of customers such as customer loyalty on brand (Heidari, Alibeigi, & Aghaeifar, 2016), customer loyalty on service quality (Liu & Wang, 2017), effect of marketing mix on customer loyalty (Azimi, 2017) or other factors affected on customer loyalty (Worku, 2019), customer loyalty is a desired and essential result for companies in a business environment with a lot of competition, of which the fashion industry is no exception (Khoa, 2020) and etc. Though these papers don"t mention directly on employee loyalty, they provide some suggestions for researching on loyalty.…”
Section: Nomentioning
confidence: 99%